CURRENT MORPHOLOGICAL ACHIEVEMENTS IN UNDERSTANDING OF URINARY BLADDER PATHOLOGIES AND THEIR DETAILED ANALYSIS - Starchenko І.І.; Коробчанська, А.Б.; Vynnyk, N.I.; Koptev, M.M.; Sovgirya, S.M. (World of Medicine and Biology, 2018)
The paper presents the analysis of the current studies of the urinary bladder pathologies that occur in the clinical practice. The novel theories of the UB damage and the disorders of the urodynamics are impressive by its complexity and diversity. Understanding the causes and ways of the development of UB pathological processes is crucial in the correct and timely diagnosis and further therapeutic management, resulting in the improving of patient’s quality of life. In particular, the analysis and study of some of the discoveries made by the scholars that form an understanding of the development of inflammatory, nonplastic and dysfunctional pathology of the bladder is presented. The paper highlighted the differential diagnosis of the inflammatory pseudotumor, pathogenesis of the overactive bladder, clinical and morphological picture of rare malignant tumors. The role of the advanced morphological studies in the diagnosis of the UB disease is emphasized.